2005
DOI: 10.4070/kcj.2005.35.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Stenting with Distal Protection Device: Early Experience

Abstract: Background and Objectives:Carotid artery stenting (CAS) is emerging as a reasonable alternative to carotid endarterectomy, and especially for those patients with comorbidities. However, this endovascular approach has acute complications related to distal embolization. Therefore, the use of protection devices is expected to reduce the risk of embolic strokes during this procedure and to deliver more favorable outcomes. We report here on our early experiences with balloon occlusion and filter type distal protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“… 1 - 4) Carotid artery stenting has emerged as an alternative treatment to carotid endarterectomy for this common disorder. 5 - 7) The SAPPHIRE investigators reported that carotid stenting was not inferior to carotid endarterectomy for the treatment of carotid artery stenosis at 3 years. 8) …”
Section: Discussionmentioning
confidence: 99%
“… 1 - 4) Carotid artery stenting has emerged as an alternative treatment to carotid endarterectomy for this common disorder. 5 - 7) The SAPPHIRE investigators reported that carotid stenting was not inferior to carotid endarterectomy for the treatment of carotid artery stenosis at 3 years. 8) …”
Section: Discussionmentioning
confidence: 99%